The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/1518-8345.3049.3151
|View full text |Cite
|
Sign up to set email alerts
|

Enfermeiros na triagem no serviço de emergência: autocompaixão e empatia

Abstract: Objetivo: este estudo adaptou e validou a escala Consultation and Relational Empathy Measure (versão brasileira) para avaliação da empatia por enfermeiros; avaliou a concordância entre empatia autorreferida pelos enfermeiros e a percebida pelos pacientes e correlacionou autocompaixão com empatia autorreferida dos enfermeiros e percebida pelos pacientes. Método: sete juízes validaram a adaptação da escala citada para a Consultation and Relational Empathy Measure Nurses (versão brasileira) com anuência do autor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
0
7
0
6
Order By: Relevance
“…They confirmed that higher self-compassion was associated with higher levels of compassionate care for patients. Savieto et al 48 examined whether selfcompassion among nurses working in the Accident and Emergency Department was associated with empathic care as objectively evaluated by their patients. They found that nurses with higher self-compassion provided more empathic care.…”
Section: Discussionmentioning
confidence: 99%
“…They confirmed that higher self-compassion was associated with higher levels of compassionate care for patients. Savieto et al 48 examined whether selfcompassion among nurses working in the Accident and Emergency Department was associated with empathic care as objectively evaluated by their patients. They found that nurses with higher self-compassion provided more empathic care.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of a death among those who were screened as a low priority by nurses during the rapid triage is highlighted. For this case, the MTS was suffering/anguish (16) . There is also the insecurity of the professionals in relation to the possibility of deterioration of the clinical condition of the patient awaiting care and the tensions arising from hostile acts by patients and/or family members.…”
Section: Still In the Case Of Patients Classified In The Redmentioning
confidence: 96%
“…A empatia e a compaixão são características essenciais para o processo de aprendizado da profissão enfermagem. Sendo imprescindíveis para o estudante, porém esta é uma habilidade que pode ser ensinada e, consequentemente, aprendida 23 .…”
Section: Categoria Temática 2: Uma Reflexão Sobre Empatia E Enfermagemunclassified